GC-MS based bioactive profiling of Phyllanthus niruri and its antibacterial potential through experimental and computational studies - Zubair Khalid Labu; Samira Karim; Maria Afroz; Umme Kulsum Batul; Lina Akther; Md. Tarekur Rahman; Sarder Arifuzzaman (PLoS ONE, 2026)
Objective The study aimed to evaluate the antibacterial potential of Phyllanthus niruri by identifying its bioactive compounds through GC–MS, assessing their in vitro antibacterial efficacy, and validating their interactions with bacterial target proteins through molecular docking and pharmacokinetic analyses. Methods Methanolic extracts were prepared and fractionated into petroleum ether (PSF), chloroform (CSF), carbon tetrachloride (CTF), ethyl acetate (ESF), methanol (MSF), and aqueous (AQF) fractions using the Kupchan method. Phytochemical screening, total phenolic content (TPC), and total flavonoid content (TFC) were determined spectrophotometrically. GC–MS analysis identified volatile constituents in the methanol extract. Antibacterial activity was evaluated against nine bacterial strains using the disc diffusion assay, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) tests. Molecular docking (PyRx), ADMET (pkCSM), and drug-likeness (SwissADME) analyses were performed to assess pharmacological suitability. Results Phytochemical screening confirmed the presence of major secondary metabolites such as flavonoids, tannins, and phenolics. The methanol fraction (MSF) exhibited the highest TPC (119.10 ± 0.11 µg GAE/g) and TFC (128.01 ± 0.11 µg QE/g), followed by the ethyl acetate fraction (TPC = 102.06 ± 0.11 µg GAE/g; TFC = 109.09 ± 0.21 µg QE/g). GC–MS profiling revealed 75 compounds, including 3,4-dimethoxy-dl-phenylalanine (13.24 µg/mL), benzeneacetamide (3,4-dimethoxy-, 13.24 µg/mL), and 3-(3,4-dimethoxyphenyl)-propionic acid (13.24 µg/mL). In vitro assays demonstrated that the methanolic and ethyl acetate fractions exhibited the strongest antibacterial activity, with inhibition zones of 33.2 ± 0.96 mm and 15.1 ± 0.52 mm against Escherichia coli and Staphylococcus aureus , respectively. MIC values ranged from 62.5 µg/mL to 250 µg/mL, and MBC/MIC ratios ≤ 4 confirmed potent bactericidal activity. Molecular docking revealed strong ligand protein affinities, with benzeneacetamide (–9.4 kcal/mol) and 3-(3,4-dimethoxyphenyl)-propionic acid (–8.7 kcal/mol) showing the highest binding energies toward DNA gyrase and penicillin-binding protein 1B (PBP1B). ADMET and SwissADME analyses indicated favorable gastrointestinal absorption, no hepatotoxicity, and compliance with Lipinski’s rule of five. Conclusion Phyllanthus niruri , particularly its polar fractions, possesses potent antibacterial phytochemicals validated through GC–MS, in vitro , and in silico studies. These findings establish its potential as a promising natural source for the development of novel antimicrobial drugs.